Escherichia coli Capsule Bacteriophages II. Morphology - Stirm, Stephan (1971)
The Escherichia coli capsule bacteriophages (K phages) described herein are specific for certain capsular strains of E. coli, all of them test strains for different E. coli K antigens. The phages are not adsorbed to the acapsular mutants of their host organisms nor to similar strains with serologically and chemically different capsular polysaccharides. Thirteen E. coli (and one Klebsiella) K phages were visualized in the electron microscope. Most viruses are similar to P22 and thus belong to Bradley group C; however, one each of group A (long, contractile tail) and group B (long, noncontractile tail) was also found. All K phages were seen to carry spikes but no tail fibers were detected. These results suggest that the structures responsible for the recognition of the thick (about 400 nm or more) capsular polysaccharide gels are located in these spikes.